Overage labor, intergenerational financial support, and depression among older rural residents: evidence from China - Yongjie Chen; Yongjie Chen; Kun Wang; Jinxu Zhao; Zixian Zhang; Jiangyin Wang; Li He (Frontiers Media S.A., 2023)
BackgroundDepression is a major factor affecting the happiness of older rural residents. With the increasing aging of the Chinese population, overage labor is becoming more prevalent in rural areas of China. This study aimed to assess whether, and if so, how, overage labor affects depression status in older rural residents.MethodsUsing data from the China Health and Retirement Longitudinal Study, this study explored the association between overage labor and depression among older rural residents by using ordinary least squares and moderated mediation models.ResultsThe results show that overage labor significantly reduced levels of depression in older rural residents. This result remained robust after using propensity score matching and double machine learning. Furthermore, the improvement of older rural residents' depression via overage labor is mainly achieved through work income, but this mediating effect is negatively moderated by intergenerational financial support. This implies that in traditional Chinese rural society, intergenerational financial support from children plays an important role in reducing depression among older rural residents.ConclusionOur findings have potential policy implications for China and other developing countries in terms of addressing issues related to aging and depression in older adults.